Pelatihan Pengelolaan Koperasi KD/KMP di Kabupaten Mojokerto dalam Menyiapkan SDM yang Kompeten Melalui Manajemen Operasional dan Model Bisnis Berbasis Potensi Desa - Kasnowo, Kasnowo; Armin, Rini (Fakultas Ekonomi Universitas Islam Majapahit, 2026)
This community service activity aims to improve the competency of the managers of the Koperasi Desa Kelurahan Merah Putih (KD/KMP) in Mojokerto Regency through operational management training and the preparation of a village potential-based business model. The activity was carried out in collaboration with the Mojokerto Regency Cooperative Office using lecture, discussion and question and answer methods. The location of the activity was themed on Friday, November 7, 2025 at New Djimbaran Resto and Friday, November 21, 2025 at Amanatul Ummah Pacet, Mojokerto Regency. This training provides an understanding of operational management that discusses planning, organizing, implementing, and supervising business activities effectively and efficiently. While the material challenges the village potential-based model, namely identifying village potential through the Business Model Canvas, and sustainable cooperative business development strategies.